A new species of the genus Opisthotropis Günther, 1872 from northern Laos (Squamata: Natricidae) - Teynié, Alexandre; Lottier, Anne; David, Patrick; Nguyen, Truong Quang; Vogel, Gernot (Zootaxa, 2014)
Two specimens, a male and a female, of the genus Opisthotropis Günther, 1872 were collected in a karst formation of northern Louangphabang (or Luang Prabang) Province, North Laos. These specimens are assigned to the genus Opisthotropis on the basis of their morphology, dentition and cephalic scalation. However, they differ from all other known species of Opisthotropis by a combination of the following characters: (1) 21–19 scale rows on the fore part of the body, (2) 17 scale rows at midbody, (3) 22/23 maxillary teeth, (4) 177–181 ventrals, (5) 1 loreal on each side, in contact with internasal, (6) 7 supralabials, 4th entering orbit, (7) dorsum dark bronze-brown, with upper part of dorsum darker than lateral sides, without bands or crossbars, and (8) chin and throat blackish-brown with a sharp, transversal limit with the ventral colour crossing the posterior part of the throat. As a consequence, these specimens are here referred to a new species, Opisthotropis durandi spec. nov. The new species is compared with other species of the genus, especially the most similar species O. spenceri Smith, 1918 and O. atra Günther, 1872, the type species of the genus. An updated key to the genera Opisthotropis is provided. Opisthotropis durandi spec. nov. represents the first confirmed record of a species of Opisthotropis sensu stricto from Laos and it is the 108th snake species currently recorded from the Lao People’s Democratic Republic.